THE CORRELATION OF PD-L1 EXPRESSION IN CYTOLOGICAL AND HISTOLOGICAL MATERIAL OF SEROUS HIGH-GRADE OVARIAN CANCER - Jovanović, Ljubiša; Ćirković, Anđa; Nikolić, Ljubinka; Jović, Milena; Mikić, Darko; Milenković, Svetlana; Janković, Radmila (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Neoplastic cells in peritoneal lavage express various proteins with significant prognostic and therapeutic potential. Such expression could differ from the expression in a primary tumor or in metastases. In this research, we compared PD-L1 (programmed cell death ligand-1) expression on ovarian cancer cells in cytological material with its expression on peritoneal metastases and a primary tumor. Materials and methods: The study included 30 patients who had been operated on for high-grade serous ovarian cancer (HGSC) in FIGO IIIC, over the period of one year. Cytoblocks, cytological and tissue microarrays were assembled and immunostained with PD-L1 antibody. For each tumor compartment we determined four PD-L1 expression categories: negative, low, moderate, and strong expression, according to the percentage of membrane positive tumor cells. Moderate and strong positivity together were considered as high PD-L1 expression. Results: Moderate PD-L1 expression was the most frequent pattern in primary HGSC (50%) and in peritoneal metastases (omentum) (60%). Cytological samples mostly showed low PD-L1 expression (57%). Statistical analysis did not show a significant difference in PD-L1 expression between the study groups. We found a positive correlation of PD-L1 expression between different, matched tumor samples in every patient, with statistical significance (p
Keywords: ovarian carcinoma; PD-L1; peritoneal lavage; metastases